Evaluation of water supply function in the Economic Belt of the Northern Slope of the Tianshan Mountains based on the InVEST model - Wei Liu; Hao Tian; Xingang Xu; Guang Yang (Climate Services)
The Economic Belt of the Northern Slope of the Tianshan Mountains (EBNSTM) is a composite ecosystem with mountains, oases, and desert areas; it also serves as an active area for anthropogenic activities. Frequent changes in soil and water resources have significant impacts on regional ecosystems. However, research on the ecosystem water yield function of EBNSTM is relatively limited; additionally, the spatiotemporal variations in the water supply function based on land use changes have not been sufficiently elucidated. This study aimed to explore the land use changes and the spatial variability of water supply service functions in the region at the macro level and uses the land transfer matrix as an important tool to study the changes in land use in the different years of 2000, 2005, 2010, 2015, and 2020. Using the InVEST model, we conducted a quantitative assessment and comprehensive study on the water supply function of EBNSTM across the aforementioned years. Additionally, the study delved into the structure of ecosystem service functions, alongside investigating the spatial and temporal variability of ecosystem services under the multi-scale units of administrative divisions, ecological zones, and land classes. We found that during the 20-year period, the area of construction land of EBNSTM increased by 1089 km2, with the highest dynamic change rate of 4.09 %; 2015–2020 period was the most drastic period of change for each land use type. The average multi-year depth of water production was 87.49 mm, totaling 71.59 × 108 m3. The spatial distribution pattern of the water supply function in the study area during the last 20 years consistently exhibited a distinct pattern: mountainous areas displayed the highest water supply capacity, followed by oases, and deserts ranked the lowest. Further, the water supply service function within the study area is currently experiencing a modest rate of increase. The rate of change in water supply depth was 2.76 mm/a, while the rate of change in water supply volume was 0.47 × 108 m3/a. Areas with enhanced water supply capacity are mostly distributed in the southeast of EBNSTM, whereas the northwest, encompassing the mountainous areas, exhibited a declined water supply capacity. Between 2000 and 2020, the water supply capacity in the study area was ranked as follows: woodland > grassland > unutilized land > cultivated land > urban construction land, with woodland displaying the strongest water supply capacity. When woodlands, grasslands, and croplands were converted to other land use types, their water supply functions generally decreased, and vice versa. Our findings provide a scientific basis for the sustainable management of water and soil resources in EBNSTM.